KOORDINASI PENYUSUNAN RENCANA PEMBANGUNAN DI DESA ANGKARAS KECAMATAN MENYUKE KABUPATEN LANDAK - E.01105036, Adewanto (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Journal writing is intended to provide fill to the public on the implementation of development plans through Deliberation village development plan (musrenbangdes). About the lack of participation of village officials and representatives of civil society organizations that exist in this country to follow the implementation Musrenbangdes, there are the village officials and representatives of the civil society organizations that are not involved in the implementation and therefore contributes to musrenbang contributions to the proposed development program, still disputes / conflicts among the officers who attend the meeting planning forums in the village in terms of proposed development program.Â  Through journal writing is also intended in this activity should angkaras village chief who is considered as the coordinator of all activities of the Development of its territory must be able to fight or memeprtahankan any proposed development programs originating from its territory that any proposed development program proposed to the Government level, District / Province can be realized according to the aspirations and needs of the village community Angkaras.Keywords: Coordination, Development Planning, Village planning forums.